The Influence of Social Media on Palestinian Secondary Schools English Writing Skills from English Teachers’ Perspectives in Jenin Region - Tahani R. K. Bsharat; Fariza Behak (Institut Agama Islam Negeri Madura, 2021)
Writing skills play a crucial role in this modern world, and one must develop these skills to excel in teaching-learning processes. Therefore, writing becomes one of the most important abilities of all four language skills to communicate effectively in this global environment. Since English is commonly used throughout the world, learners need to acquire their writing skills to be effective in their respective fields. The teachers have to consider and seek to incorporate different teaching methods, especially social media, during these challenging times with the presence of COVID 19. This study aimed to find out the influence of social media on Palestinian secondary schools' English writing skills from teachers' perspectives in the Jenin region, and also the influence of (gender, academic qualification, and years of experience) variables in the influence of social media on Palestinian secondary school's English writing skills from teachers' perspectives in the Jenin region. The study sample consists of (30) Palestinian secondary schools English language teachers who will select randomly in the scholastic year (2019-2020). Thus, the researcher adopted the descriptive-analytic approach (quantitative method). The results show that a negative influence of social media on Palestinian secondary schools students' English writing skills